NCJR Annual Report: 2016 - Spohn, Ryan E. (2016)
The Nebraska Center for Justice Research (NCJR) was established in 2014 with a mission to develop and sustain criminal justice research capacity internal to the State of Nebraska. Our goal is to assist the Legislature, justice agencies, practitioners, foundations, and stakeholders with research and evaluation to reduce recidivism, promote the use of evidence-based practices, and improve public safety. This annual report summarizes the activities and financial status of NCJR in its second year